Conveyed leader PsyCap predicting leader effectiveness through positive energizing - Rego, J. (2020)
Whereas past research on psychological capital (PsyCap) has tended to focus on how one’s self-attributed PsyCap affects one’s work behaviors, we extend this literature by examining the concept of conveyed PsyCap and its downstream consequences, above and beyond the influence of self-attributed PsyCap. Drawing from the emotions-as-social-information model, we tested a model of conveyed leader PsyCap predicting leader effectiveness through team positive energizing. A laboratory experiment and a multisource study provided support for our hypotheses. We furthermore found that a leader’s within-team consistency in conveyed PsyCap moderates these effects, such that leaders who are more consistent in conveyed PsyCap are rated by followers as better leaders, via the mediating effect of team positive energizing. A post hoc analysis further suggests that conveyed PsyCap is more consistent when conveyed PsyCap is congruent with self-attributed PsyCap. Our work contributes to a better understanding of the underlying mechanisms that make leaders with greater conveyed PsyCap more effective and advances the conceptualization and measurement of PsyCap.